Ivermectin electrochemical behavoiur at glassy carbon electrode - Selaković, Milan; Aleksić, Mara; Ivković, Branka (Archives of Pharmacy, 2022)
Ivermectin (IVM) is a drug from the group of anthelmintics used in veterinary and human medicine. Recently, it has been used in the treatment of some malignant diseases, as well as viral infections caused by Zika virus, HIV-1, SARS-CoV-2, which has increased the interest in this medicine. Electrochemical characterization of IVM was done with the aim of better understanding the redox behavior of the molecule, as well as to predict potential transformations during interactions with other electroactive biomolecules. Electrochemical behavior was examined by cyclic (CV), differential pulse (DPV) and square wave voltammetry (SWV) using a glassy carbon electrode (GCE). The effect of pH was examined in the pH range 2–10. The results confirmed that IVM is electroactive in the entire study area. IVM shows the main oxidation peak at a potential of about 1.0 V, which is most intense in a neutral environment, and an additional (weakly expressed) peak, due to oxidation of the reduced drug form. In voltammograms, there is also a peak of low intensity, which originates from the reduction of the previously oxidized form of the drug. Based on the shape of the voltammogram, it is concluded that all these processes are irreversible. The analysis of the influence of the rate of change of potential (pH 4.6 and 7.0) is also responsible for the adsorption of the active component on the electrode. The presented results indicate the advantage of applying electrochemical methods in drug analysis due to low cost, high speed and ease of execution